Synthesis and characterization. of ZnS@Fe3O4 fluorescent-magnetic bifunctional nanospheres - Koc, Kenan; Karakus, Baris; Rajar, Kausar; Alveroglu, Esra (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2017)
Herein, we synthesized and characterized fluorescent and super paramagnetic ZnS@Fe3O4 nanospheres. First, (3-mercaptopropyl) trimethoxysilane (MPS) capped ZnS quantum dots (QDs) and SiO2 coated Fe3O4 nanoparticles were synthesized separately by using solution growth and co-precipitation techniques. After synthesis and characterization of these two nanoparticles, they were conglutinated together in a nano sized sphere. The QDs were attached to the surface of the Fe3O4 nanoparticles by Si-O-Si bonds and so Si-O-Si bonds created a SiO2 network around the nanoparticles during the formation of the ZnS@Fe3O4 nanospheres. The synthesized MPS capped ZnS fluorescent QDs, SiO2 coated magnetite super paramagnetic nanoparticles and ZnS@Fe3O4 fluorescent-magnetic bifunctional nanospheres were characterized by using UV-Vis Absorption Spectroscopy, Fluorescence Spectroscopy, X-ray analysis, Vibrating Sample Magnetometer analysis, Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy, Scanning Electron Microscope and Energy-dispersive X-ray spectroscopy. ZnS@Fe3O4 bifunctional nanospheres were shown to retain the magnetic properties of magnetite, while exhibiting the luminescent optical properties of ZnS nanoparticles. The combination of fluorescent and magnetic behaviors of nano composites make them useful for potential applications in the field of bio-medical and environmental. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Magnetic nanoparticle; Semiconducting nanoparticle; Nanostructure; STRUCTURAL-PROPERTIES; NANOPARTICLES; NANOCOMPOSITES; ZNS; 3-MERCAPTOPROPYLTRIMETHOXYSILANE; KINETICS; GROWTH; Physics